Sistem Pendukung Keputusan Penerima Beasiswa Tidak Mampu Menggunakan Metode Moora - Yusni Amaliah; Suprianto suprianto (Universitas Asahan, 2021)
Abstract - The process of distributing scholarship funds often occurs education of in the world, one of which is the lack of targets in the admission process. There are several criteria that must be met by school students in determining scholarship recipients, including the condition of the house to live in, water and electricity facilities, parents' income and the vehicle used to go to school. Therefore, an effective method is needed in determining which students are eligible to receive underprivileged scholarships, namely Multi Objective Optimization on the Basis of Ratio. This method has criteria and sub criteria as well as a weighted value that is given based on the importance of these criteria. Based on the calculation results, 6 data were obtained as scholarship recipients with a value range between 25 s / d 27 which is the highest value of each criteria.Keywords - Decision Support System, scholarship, Moora. Abstrak – Proses penyaluran dana beasiswa masih sering terjadi dalam dunia pendidikan salah satunya yaitu kurang tepat sasaran dalam proses penerimaannya. Terdapat beberapa kriteria yang harus dipenuhi oleh siswa sekolah dalam menentukan penerima beasiswa, antara lain keadaan rumah tempat tinggal, fasilitas air dan listrik, penghasilan orang tua serta kendaraan yang digunakan untuk berangkat ke sekolah. Tujuan penelitian ini adalah membantu Dinas Sosial dalam menentukan siswa yang layak menerima beasiswa tidak mampu. Dalam proses pengambilan keputusan tersebut digunakan metode Multi Objective Optimization on the Basis of Ratio. Berdasarkan hasil perhitungan, maka diperoleh 6 (enam) data siswa sebagai penerima beasiswa dengan range nilai antara 25 s/d 27 yang merupakan nilai tertinggi dari setiap kriteria.Kata Kunci - Sistem Pendukung Keputusan, Beasiswa, Moora.